An analytical nonlinear displacement model of electrothermal V-shaped actuator - Hoang, Kien Trung; Ham, Vu Cong; Pham, Phuc Hong; Phuc, Truong Duc (Vietnam Journal of Mechanics, 2024)
This work presents an analytical model to determine nonlinear displacements of electrothermal V-shaped actuators. The nonlinear displacement model of V-shaped beams fixed at both ends is established based on considering the axial deformation of the beam. The 3D model of the V-shaped microactuator was established to verify the theoretical nonlinear model. The evaluation shows that the displacement deviation between the analytical nonlinear model and simulation is approximately 7.7% at the driving voltage of 16 V. This confirms the advantages of the proposed model to predict more precisely the displacement of the electrothermal V-shaped actuator.